Severe effects of Escherichia coli and Enterococcus faecalis on hatchability and first-week performance following inoculation of 18-day-incubated embryonated broiler eggs - T.T.M. Manders; J.J. de Louwere; R. Meijerhof; A. Nangsuay; M. van de Beek; L. van der Graaf-Bloois; A.L. Zomer; F. Vargas; J.J. de Wit (Poultry Science, 2025)
In ovo vaccinations have been widely used in the poultry industry over the past three decades. During vaccination, various factors, including bacterial contamination of embryonated eggs, can negatively affect hatchability, chick quality and first-week performance. The aim of this study was to assess the effect of inoculation with different bacteria at incubation day 18 on hatchability, chick quality and first-week mortality. Furthermore, the effects of different bacterial doses on the same parameters were assessed.First, inoculation strains were selected by isolating bacteria from unhatched, in ovo-vaccinated eggs in commercial hatcheries. A total of 23 bacteria species were isolated, with E. coli and E. faecalis being the most commonly found species in eggs from all hatcheries. The virulence of ten E. coli and ten E. faecalis isolates was assessed using an embryo lethality assay. Subsequently, the most virulent strains of E. coli and E. faecalis were selected for an animal experiment. Eighteen-day incubated embryonated broiler eggs were inoculated with 0.1 ml of bacteria suspension or peptone physiological saline, using 36 eggs per group. Three different bacterial doses (102, 104 or 106 colony-forming unit/egg) were used. Hatching rate, time of hatch, chick length, and Pasgar score were determined at the end of the incubation process and mortality, time of death, and chick weight in the first week of life.Hatchability did not significantly differ between the different doses when E. faecalis was inoculated, ranging from 56 to 69 %. First-week mortality in these groups ranged from 36 to 86 %, while chick quality did not differ from the control groups. E. coli was pathogenic at all tested doses, with no chicks hatching in any of these groups. In all groups (E. coli and E. faecalis), severe drops in hatchability and increased first-week mortality were observed. Therefore, strict hygiene measures should be implemented in hatcheries during in ovo vaccination to prevent contamination of eggs with low numbers (<102 cfu/egg) of virulent bacteria, such as E. coli and E. faecalis.